2019
DOI: 10.1007/s10750-019-3953-4
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Mysis relicta (Mysida) reduces niche segregation between deep-water Arctic charr morphs

Abstract: Niche diversification of polymorphic Arctic charr can be altered by multiple anthropogenic stressors. The opossum-shrimp (Mysis relicta) was introduced to compensate for reduced food resources for fish following hydropower operations in Lake Limingen, central Norway. Based on habitat use, stomach contents, stable isotopes (δ 13 C, δ 15 N) and trophically transmitted parasites, the zooplanktivorous upper water-column dwelling 'normal' morph was clearly trophically separated from two sympatric deep-water morphs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…In Arctic charr, the development of resource polymorphisms is common and in the absence of competition from other species may develop into stable niches under conditions of intense intra‐specific competition (Jonsson & Jonsson, 2001). Notably absent in the Kerguelen sample was any suggestion of morphological variation, which has been described extensively from both North American (Guiguer et al ., 2002; Power et al ., 2012) and European lakes ( e.g ., Hindar & Jonsson, 1982; Klemetsen et al ., 2003; Knudsen et al ., 2019; Pavlov, 1997; Snorrason et al ., 1994). Time may explain the absence of morphological and feeding correlates, although examples of the incipient divergence of traits related to prey use in contemporary time frames exist ( e.g ., Michaud et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Arctic charr, the development of resource polymorphisms is common and in the absence of competition from other species may develop into stable niches under conditions of intense intra‐specific competition (Jonsson & Jonsson, 2001). Notably absent in the Kerguelen sample was any suggestion of morphological variation, which has been described extensively from both North American (Guiguer et al ., 2002; Power et al ., 2012) and European lakes ( e.g ., Hindar & Jonsson, 1982; Klemetsen et al ., 2003; Knudsen et al ., 2019; Pavlov, 1997; Snorrason et al ., 1994). Time may explain the absence of morphological and feeding correlates, although examples of the incipient divergence of traits related to prey use in contemporary time frames exist ( e.g ., Michaud et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Lake Limingen (64 • 42 13 N, 13 • 32 40 E) is located in central Norway in Trøndelag county while the remaining four lakes are located in Troms county in Northern Norway (Figure 1). These lakes have been described in other work (Klemetsen et al, 1997;Smalås et al, 2013;Knudsen et al, 2019;Moccetti et al, 2019) and the following is an overview of previous descriptions. Lakes in Troms county are typically ice covered from November/December to May/June and are described as being dimictic and oligotrophic (Klemetsen et al, 1997;Smalås et al, 2013;Moccetti et al, 2019).…”
Section: Lake Description and Fish Collectionmentioning
confidence: 96%
“…trimorphic Arctic charr (LO, PB, and PP) and brown trout and is 53 m deep and 3.21 km 2 (Moccetti et al, 2019). Lake Limingen has a surface area of 95.7 km 2 and a maximum depth of 192 m. It is described as being dimictic and oligotrophic and contains in addition to the trimorphic Arctic charr (LO, PB, and PP), brown trout, minnow (Phoxinus phoxinus L. 1758; introduced in 1980s), and three-spined stickleback (Knudsen et al, 2019).…”
Section: Lake Description and Fish Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect was ascribed to differences in foodchain length that was longer in the monomorphic whitefish lakes, and the keystone predator role of Arctic charr in the monomorphic whitefish lakes. Second, Knudsen et al (2019), examining the impacts of anthropogenic stressors on polymorphic Arctic charr, noted that introduction of the opossum-shrimp Mysis relicta (Lovén 1862) had reduced ancestral niche segregation between or among two deep-water morphs and thereby increased resource competition, and possibly, the risk of hybridization. Third, Henriksen et al (2019) found that growth rate of Arctic charr was linearly related to abundance of a less harmful parasite, Crepidostomum spp., and non-linearly related to abundance of a more harmful parasite, Eubothrium salvelini (Schrank 1790), perhaps because the negative effect of a high-cost parasite was outweighed by the energy gained from feeding on the intermediate host.…”
Section: Trophic Ecologymentioning
confidence: 99%